ROS-AMPK/mTOR-dependent enterocyte autophagy is involved in the regulation of Giardia infection-related tight junction protein and nitric oxide levels - Wu, Jingxue; Yang, Yongwu; Liu, Lin; Zhu, Weining; Liu, Min; Yu, Xiran; Li, Wei (Frontiers in Immunology, 2023)
Giardia duodenalis, a cosmopolitan noninvasive protozoan parasite of zoonotic concern and public health importance, infects the upper portions of the small intestine and causes one of the most common gastrointestinal diseases globally termed giardiasis, especially in situations lacking safe drinking water and adequate sanitation services. The pathogenesis of giardiasis is complex and involves multiple factors from the interaction of Giardia and intestinal epithelial cells (IECs). Autophagy is an evolutionarily conserved catabolic pathway that involves multiple pathological conditions including infection. Thus far, it remains uncertain if autophagy occurs in Giardia-infected IECs and if autophagic process is associated with the pathogenic factors of giardiasis, such as tight junction (TJ) barrier defects and nitric oxide (NO) release of IECs. Here Giardia-in vitro exposed IECs showed upregulation of a series of autophagy-related molecules, such as LC3, Beclin1, Atg7, Atg16L1, and ULK1, and downregulation of p62 protein. IEC autophagy induced by Giardia was further assessed by using autophagy flux inhibitor, chloroquine (CQ), with the ratio of LC3-II/LC3-I significantly increased and downregulated p62 significantly reversed. Inhibition of autophagy by 3-methyladenine (3-MA) rather than CQ could markedly reverse Giardia-induced downregulation of TJ proteins (claudin-1, claudin-4, occludin, and ZO-1; also known as epithelial cell markers) and NO release, implying the involvement of early-stage autophagy in TJ/NO regulation. We subsequently confirmed the role of ROS-mediated AMPK/mTOR signaling in modulating Giardia-induced autophagy, TJ protein expression, and NO release. In turn, impairment of early-stage autophagy by 3-MA and late-stage autophagy by CQ both exhibited an exacerbated effect on ROS accumulation in IECs. Collectively, we present the first attempt to link the occurrence of IEC autophagy with Giardia infection in vitro, and provides novel insights into the contribution of ROS-AMPK/mTOR-dependent autophagy to Giardia infection-related downregulation of TJ protein and NO levels.